Estudo das propriedades reológicas de nanocompósitos para a produção de filmes tubulares - Beatrice, Cesar Augusto Gonçalves (Universidade Federal de São Carlos, 2008)
In this work, the use of rheological measurements in substitution or complementation to methods normally employed in the characterization of nanocomposites, such as X-ray diffraction (WAXS) and transmission electron microscopy (TEM), was evaluated. Two polymeric matrices with different chemical structures and polarities and two organophilic nanoclays modified with organic surfactants, which were compatible with the respective polymer matrix, were used. Thus, polyamide 6 (PA6) and high density polyethylene (HDPE) nanocomposites were obtained by melt mixing and blown as films. WAXS measurements showed intercalated structures in the HDPE nanocomposites and exfoliated structures in the PA6 nanocomposites. Shear oscillatory rheological experiments were done to evaluate the clay dispersion and distribution in the polymer matrices, which indicated the presence of a poor dispersion in the HDPE nanocomposites, differently of the PA6 nanocomposites. Shear steady and transient rheological measurements indicated that higher interactions between PA6 and the nanoclay modified with a polar surfactant and inside the EVA masterbatches occurred. From the rheological, morphological, mechanical and transport analysis it was found that the addition of clay modified the interfacial interactions between HDPE and EVA, increasing the system compatibility. In both systems, there was an increase in elastic modulus, yielding and rupture behaviors and barrier properties. In conclusion, the rheological characterization of nanocomposites provides further information about the nanoclay dispersion and distribution in the polymer matrix, in addition to quantify the interactions between the components. However, it can not substitute the usual methods of characterization of the nanocomposites, such as WAXS and TEM.
Rheological characterization of nanocomposites for a blown film extrusion process
Keywords: Reologia; Nanocompósitos; Filmes tubulares; Processo de extrusão; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA